The Constitutional Dilemmas on Cases of Incompatibility and Conflict of Interest of Members of Parliament in Albania - Fjorida Ballauri (European Scientific Journal, ESJ, 2026)
This paper examines the constitutional and statutory framework governing parliamentary incompatibility in the Republic of Albania, with particular emphasis on conflict of interest and the protection of public office integrity. The analysis centers on Article 70 of the Constitution and the Law on the Prevention of Conflict of Interest, which imposes restrictions on members of parliament and persons related to them. The central research question is whether statutory incompatibility may constitute a valid legal ground for the termination of a parliamentary mandate. To address this issue, the study analyzes the jurisprudence of the Constitutional Court, the limitations imposed on the private interests of deputies and related persons, and the respective roles of the Assembly and the High Inspectorate for the Declaration and Audit of Assets and Conflict of Interest. The research employs a doctrinal methodology based on the systematic and hierarchical interpretation of constitutional and statutory norms, complemented by a limited comparative perspective drawing on selected European models and international standards (GRECO, Venice Commission, OSCE). The findings indicate that, despite the existence of an extensive normative framework, inconsistencies in practical application and ambiguities in the allocation of powers between the Assembly and the Constitutional Court have undermined the establishment of a coherent and unified standard for parliamentary incompatibility. The paper concludes by emphasizing the need for clearer legal regulation of incompatibility cases, enhanced inter-institutional coordination, and strengthened control mechanisms to ensure effective implementation of the principles of parliamentary integrity and accountability in Albania.